Zen in Distress: Theorizing Gender Dysphoria and Traumatic Remembrance within Sōtō Zen Meditation - Buckner, Ray (Religions, 2020)
Gender dysphoria is considered a pronounced experience of distress in the bodies and minds of some transgender people. Examining the text Zen Mind, Beginners Mind by Shunryū Suzuki, I analyze some of the difficulties that may arise for transgender practitioners experiencing acutely strong gender dysphoria within the Sōtō Zen meditation experience. I seek to understand how physical and psychological gender distress may make concentration, and thereby realization, challenging and potentially harmful within a context of Sōtō Zen meditation. I consider how meditation can exacerbate the panic and traumatic remembrance of the body and mind, leading both to embodied struggles, as well as undoubtedly philosophical ones too. This paper theorizes gender dysphoria to exist beyond a state of unitary “distress” to include trauma. I put forward an understanding of gender dysphoria that is grounded in traumatic, gendered remembrances—what I call “sustained traumas.” Within the meditation experience, I argue trans, gender dysphoric people may experience heightened disconnect, separation, and deepening into their solid and suffering “self” rather than open to the fundamental nature of emptiness, non-duality, and an empty and move-able core. Ultimately, I argue meditation may lead to a deepening of traumatic remembrance, posing potential corporeal and philosophical problematics for gender dysphoric practitioners within Sōtō Zen meditation.